2005
DOI: 10.1371/journal.pmed.0020344
|View full text |Cite
|
Sign up to set email alerts
|

A Malaria Vaccine That Elicits in Humans Antibodies Able to Kill Plasmodium falciparum

Abstract: Background Plasmodium falciparum merozoite surface protein 3 is a malaria vaccine candidate that was identified, characterised, and developed based on a unique immuno-clinical approach. The vaccine construct was derived from regions fully conserved among various strains and containing B cell epitopes targeted by human antibodies (from malaria-immune adults) that are able to mediate a monocyte-dependent parasite killing effect. The corresponding long synthetic peptide was administered to 36 volunteers, with eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
156
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(164 citation statements)
references
References 38 publications
6
156
0
2
Order By: Relevance
“…Moreover, IgG1 may also down-regulate MN activation by triggering the regulatory Fc␥RIIb (51). Though IgG3 is clearly more potent, IgG1 still plays a substantial role in ADCI as shown by our results and by the effect in ADCI of Abs induced in human volunteers by the MSP-3 vaccine, which were mostly of IgG1 subclass (14). Finally, IgG1 is also far more stable and has a longer half-life than IgG3.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Moreover, IgG1 may also down-regulate MN activation by triggering the regulatory Fc␥RIIb (51). Though IgG3 is clearly more potent, IgG1 still plays a substantial role in ADCI as shown by our results and by the effect in ADCI of Abs induced in human volunteers by the MSP-3 vaccine, which were mostly of IgG1 subclass (14). Finally, IgG1 is also far more stable and has a longer half-life than IgG3.…”
Section: Discussionsupporting
confidence: 53%
“…As ADCI is an indirect mechanism of defense, we have argued that there is no direct immune pressure generating antigenic polymorphism (52). Conserved antigenic determinants offer substantial advantages for vaccine development and this is indeed the case for the MSP-3-LSP vaccine candidate recently undergoing clinical trials (14,58). Investigations into genomic and proteomic data for molecules released by erythrocytic schizonts, presenting conserved regions, and targeted by cytophilic human Abs, shall lead to the discovery of novel vaccine candidates that have not been searched for, up to now.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…MSP-3 specific antibodies found in sera from malaria-endemic areas are associated with protective immunity (Soe et al, 2004). MSP-3 based vaccines have been designed as long peptides representing the conserved C-terminus of the antigen (Druilhe et al, 2005;Sirima et al, 2007). Anti-parasite activity of MSP-3 specific antibodies was not evident unless monocytic cells were used in the assay (ADCI).…”
Section: Merozoite Surface Coat Antigensmentioning
confidence: 99%
“…These peptide immunogens were highly conservative for all plasmodium isolates; they induced formation of cytophilic antibodies of IgG1 and IgG3 subclasses; via opsonizing shizonts they attracted monocytes that caused shizont lysis (Theisen et al, 2001;Soe et al, 2004). Phase I clinical trials (Druilhe et al, 2005;Sirima et al, 2009) demonstrated formation of long (at least 1 year) immune response to these vaccines. At the moment Phase IIb clinical trial of the MSP3-LSP vaccine continues (http://www.amanet-trust.org/ext/reports /newsletters/issue23June08.pdf).…”
Section: Peptide Vaccines Against Malariamentioning
confidence: 99%